PENGGUNAAN KONTRASEPSI PADA WANITA PREMENOPAUSE DI INDONESIA: PREVALENSI DAN DETERMINAN - Riza Fatma Arifa; Dedik Sulistiawan (JURNAL KESEHATAN REPRODUKSI, 2024)
Prevalence and Determinants of Contraceptive Use Among Premenopausal Women in Indonesia: Evidence from the 2022 Indonesia National Socioeconomic Survey (SUSENAS) Background: Premenopausal women encounter distinct reproductive health challenges characterized by irregular menstrual cycles and hormonal fluctuations, making them susceptible to unwanted pregnancies and associated health problems. Understanding the contraceptive needs and preferences of premenopausal women is essential for effective family planning strategies. Objective: This study examined the prevalence and socioeconomic determinants of contraceptive use among premenopausal women.  Method: We analyzed the National Socio-Economic Survey (Susenas) 2022 data, including 126,444 premenopausal married women aged 35-49 years.  Prevalence was measured using percentages, and the factors of contraceptive use in premenopausal women were investigated using multinomial logistic regression analysis. Results: The prevalence of contraceptive use in premenopausal women was 55%. Hormonal methods, comprising 44.2%, emerged as the predominant method. A multinomial logistic regression revealed that contraceptive use was associated with age, education level, place of residence, type of insurance membership and household economic status.  Conclusion: More than half of premenopausal women in Indonesia use contraception. The type of contraception used in this population needs to be carefully examined, particularly for short-term hormonal. Comprehensive information and education regarding the side effects and impacts of each contraceptive method are important and must be provided to all prospective clients, whatever their background, before using contraception.